Lago de Furnas: os impactos econômicos nos municípios lindeiros em decorrência das oscilações do nível da represa no período de 2000 a 2020 - Ávila, Marcelo Castro (2024)
This research proposes to investigate the economic and social relevance of Lake Furnas for the neighboring municipalities; To do this, it analyzes the possible economic impacts caused by fluctuations in the volume of water dammed in the lake, as well as the sectors of the economy most sensitive to these fluctuations. It is noteworthy that this research provides a deeper and more detailed analysis of the importance of Lake Furnas in the municipalities investigated, as well as providing access to considerations about economic and social development at the municipal level. To achieve this objective, a construction of the historical context of the creation of the Furnas Hydroelectric Power Plant is presented, as well as the theoretical basis on the right to the city and the regional configuration. In a second step, a socioeconomic characterization of the neighboring municipalities is carried out based on secondary research in databases from official bodies. Through the collection of this secondary data, tabulation, use of statistical methods of bivariate and multivariate analysis and interpretation of this information, referring to the period from 2000 to 2020, quantitative and descriptive research develops relevant discussions about how the group of neighboring municipalities is organized, makes considerations of the most diversified municipal economies and also of those most vulnerable to the dam's fluctuations, points out aspects about the loss of the right to the city and culminates in the survey of variables that suffer interference from the dam's level, those that do not and others of a more complex and subjective.